Determinants of management accounting Control system in Malaysian manufacturing companies - Tuan Zainun Tuan Mat; Malcolm Smith; Hadrian Djajadikerta (2010)
This study examines the level of changes in management accounting practices (MAP)in Malaysian manufacturing companies and investigates the factors determining the change in management accounting and control systems (MACS). The data are collected using a mailed questionnaire survey to manufacturing companies in Klang Valley. Results of this study showed that, the level of management accounting practices in Malaysian manufacturing companies were consistent with the International Federation of Accountants (IFAC) frameworks on the management accounting evolution. The results also identified technological advancement and strategic change as important predictors of change in MACS. Taken together, these research outcomes make an incremental contribution to the existing management accounting change literature by providing useful insights into our knowledge of management accounting innovation specifically for developing economies